Pengaruh Influencer Marketing dan Penggunaan E-Wallet terhadap Perilaku Pembelian di TikTok Shop pada Siswa Gen Z SMA Negeri 11 Kota Jambi - Febrianti, Indri; Arpizal, Arpizal; Rifki, Ahmad (Jurnal EMT KITA, 2026)
The growth of digital transactions has driven an increase in purchasing activity on the TikTok Shop. This study aims to analyze the influence of influencer marketing and e-wallet usage on purchasing behavior. This study employs a quantitative approach using an ex post facto method. Data was collected through a survey distributed to 165 respondents selected using purposive sampling and analyzed using multiple linear regression. The results indicate that influencer marketing and e-wallet usage have a positive and significant effect on purchasing behavior. This is evident from the calculated t-value of 6.810 > the critical t-value of 1.97 and a significance level of 0.000 < 0.05, indicating that these variables have a positive and significant effect. E-wallet usage also has a positive and significant effect with a calculated t-value of 3.309 > the critical t-value of 1.97 and a significance level of 0.001 < 0.05. Simultaneously, both variables have a significant effect with a calculated F-value of 31.185 > the critical F value of 3.05 and a significance level of 0.000 < 0.05. Additionally, the coefficient of determination (R²) of 27.8% indicates that the independent variables in this study account for 27.8% of the variation in purchasing behavior. These findings indicate that a combination of promotional strategies through influencers and the convenience of digital payment systems can drive an increase in purchasing activity.